The Potential Benefits of Palm Oil Waste-Derived Compost in Embracing the Circular Economy - Geok Wee Lau; Patricia J. H. King; John Keen Chubo; Ik Chian King; Kian Huat Ong; Zahora Ismail; Tunung Robin; Imran Haider Shamsi (Agronomy)
The environmental impact of peat extraction in plant nurseries requires urgent attention due to climate change and habitat destruction. Substituting peat moss with compost derived from palm oil waste in oil palm nurseries presents a viable solution. However, the challenges in its implementation must be considered. This research focuses on optimizing composting conditions for palm oil waste and examines the impact of the compost on soil quality, nutrient availability, and seedling growth. Measurements such as the culling rate, plant height, leaf length, and chlorophyll content were taken to assess seedling growth in nurseries. The compost was also tested as a soil amendment for 5-year-old palm trees, with foliar analysis conducted to evaluate the nutrient assimilation. The results show that optimized compost significantly enhanced the seedling growth by 20–50%, evidenced by the increased plant height, longer leaf length, and higher chlorophyll content. Additionally, the foliar analysis demonstrated an improvement of 5–15% in the nutrient assimilation in the 5-year-old palm trees. This research highlights the potential of optimizing oil palm waste composting for sustainable planting media in nurseries, mitigating environmental impacts and promoting productivity in oil palm plantations. Adopting this circular economy model can address waste management challenges while ensuring a resilient and sustainable approach in the palm oil industry.